(3MGTjI Ydi GdHQOIs - (3CHhYHO Gddg eMeO Hf HgGOQ Hf YHO Gddg GdRQcTj GdTGaYjs; (3GdHhUjQj,J (B696 (3g` s ((3eMeO Hf eMeO GdQaGYj s)
(3ChdgG (B:s
(3hHYO(B: (3adeG cGf cJGH GdHQOI aj eOM CTQa GdNdb bO HdZ ZGjI GdbHhd, hfgGjI GdeCehd, cGdeKd Ch CSjQ ef GdeKd GdSGFQ bUOJ Cf CTaYgG HTQM JTQM efg GdYjhf eTJed ef GdYde Ydi cKjQ ef Gdafhf s
(3BNQgG (B:s
(3hCWQH eYWha Ydi eG QfMJ Cj heOI EWQGH MGOj GdYjS GdYjS, hbOe GdeaYhd gfG cGdChd hhbY GdXGgQ ehbY GdeVeQ dCf GdbUO GdJbOje, heY GdJbOje jJYjf GdXGgQ hGddg CYde s
(3GdfSNI HgG MhGTs
(3ocJHJ GdYfGhjf HGdMeQIs
(3hYdi ghGeT GdfSNI ebGHdGJ hJYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs